Analisis Daya Dukung Air Tanah untuk Kebutuhan Dometik dan Pariwisata di Kota Denpasar - CAHYANI, NOVIN JUWITA; DIBIA, I NYOMAN; TRIGUNASIH, NI MADE (Jurnal Agroekoteknologi Tropika (Journal of Tropical Agroecotechnology), 2018)
Analysis of the Carrying of Groundwater for Domestic and Tourism Needs in the Denpasar City This research aimed to know the carrying capacity of groundwater for domestic needs and tourism (hotel) in the Denpasar city. This research was held on November 2016 until April 2017. Primary data collection techniques was done with interviews to the people who directly need water for domestic and non domestic purposes. Determination of the respondents was conducted by purposive sampling. The number of respondents that were interviewed in this study was 100 respondents. The percentage of the population whose water needs are fulfiled from the local water company is as much as 38%, from the bore well is as much as 44% and from the dig well is as much as 18%. Most of the drinking water needs of the community in the Denpasar city use bottled water. Groundwater potential of Denpasar city based on run off coefficient calculation and groundwater basin were 13.75 million m3/year and 52.35 million m3/year. Water needs for domestic purpose of Denpasar city was 65,469,173 m3/year, while the non domestic purpose was 1,482,410.87 m3/year. Comparison between the availability of water by domestic and non domestic needs (hotel) community of Denpasar city, based on the results of the calculation of an index of carrying capacity water is. 0.9, which means the Denpasar city was included in the area that water deficit.